Experimental study of solid RC slabs strengthened on the upper surface - CAMPOS,C. O. (2018)
Abstract The current study presents the results of tests conducted in 5 reinforced concrete slabs (415 cm x 415 cm x 7 cm) in order to experimentally check the possibility of reinforcing their upper surface, as well as to assess the adhesion between the old and the reinforcing concrete layers in the slab. The main variables were the concrete and reinforcement strength deficiencies. Reference slab “L1” was tested until reaching the failure load, whereas the others were tested until reaching certain load limit, reinforced and retested until reaching the failure load. All slabs failed under bending. The strengthening increased the failure load by 30% in slabs reinforced at minimum reinforcement rate when they were compared to similar non-reinforced slabs, regardless of the original concrete strength. None of the tests conducted in the reinforced slabs showed detachments or evidence of adhesion loss between the old and reinforcing concretes.